Girls, football and emotions: a look from feminist geography (2024)
Within the work of feminist geography, it is necessary to talk about and make visible the spatial production of girls. The social construction of women from childhood places great emphasis on the geographical profile, since it  constitutes identities and subjectivities in itself. However, recent attention in geography on people’s experiences in sports has tended to focus on adult women, with little research on girls and adolescents. Therefore, it is necessary to pay attention to the importance of space and place in terms of children’s participation in sports. Feminist geography has contributed to the visibility of women inside and outside the geographical field. Within the framework of March 8 (8M) 2023, Women’s Day, I held workshops in public spaces, where girls were invited to live together, play soccer and talk about the emotions that the community generated among them. An individual diagnostic mapping of the spatial recognition of the moment was carried out, where the girls captured themselves and shared their feelings orally and in writing.